A multi-theoretical analysis of the complexity of land reform policy formulation in post- apartheid South Africa - Jurgens, Richard Bartholomew (University of the Witwatersrand, Johannesburg, 2024)
Recent years have seen a highly polarised public debate about land reform, centring on the question of whether the ANC government should seek to amend the Constitution to allow for the expropriation of land without compensation. The ANC finally adopted expropriation without compensation as its policy on land reform in 2018, a position on the question that appears to be a significant shift from its more reconciliation-led approach in the early democratic years. This dissertation analyses the land reform debate between 1994 and 2018 through a multi- theoretical lens, focusing, firstly, on the ANC-led government’s approach to policy formulation and implementation in this period, and secondly, on its approach to the parliamentary inquiry that it sponsored in 2018 to establish the public’s views on expropriation without compensation. Two related theories, the wicked problem framework, and framing theory, are used to shed light on the ANC’s approach to shaping the public debate on land reform during the period under review. An accountability model is used to evaluate the Joint Constitutional Review Committee’s approach to public engagement during its inquiry in 2018. The use of a multi-theoretical approach aims to provide new insights into the complexity of the land reform debate, and, at the same time, to illustrate the value and utility of theoretical tools in complex policy questions.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management Governance to the Faculty of Commerce, Law, and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2024
Keywords: land reform policy formulation; apartheid South Africa; SDG-11: Sustainable cities and communities